Perceived sexual harassment as a consequence of psychosocial factors (2004)
"Sexual harassment is a form of sexual violence that has become a social problem in our society, in the world, over there are accusations and counter accusations of one form of sexual harassment or the other in the work place. The academic environment is not left out of this problem, in fact, the prevalence and dimensions of the problem in the academic world is rather alarming and its effects on the psychological well-being of victims cannot be overemphasized. This study investigated the influence of personality traits (extraversion/ introversion, self-esteem) and some demographic variables (sex, age, work status, and marital status) on the perception of sexual harassment in 250 subjects from two academic communities (The University and Polytechnic of Ibadan). The result showed a significant effect of age, self-esteem. And extraversion on perceived sexual harassment, R2=. 083, F=5.37 P<.0l. Married women were also found to have higher perception of sexual harassment than single women t=2.95, df 89 P<.05 while work status has significant effect on perception of sexual harassment F(2,236) =10.4;P<.05. Riger's (1991), theory of attribution was used as a springboard in the discussion of the findings, psychological dynamics as well as implication of the findings for organization handling of harassment issues were highlighted."